1996
DOI: 10.1177/0146167296221003
|View full text |Cite
|
Sign up to set email alerts
|

Elements of the Competitive Situation that Affect Intrinsic Motivation

Abstract: Effects on intrinsic motivation of three elements of the competitive situation (viz., competitive set, competitive outcome, and inter-personal context) were explored. Participants solved puzzles with a same-sex confederate under one of five experimental inductions, and intrinsic motivation was assessed by subsequent free-choice behavior and self-reports of interest/enjoyment. As predicted by cognitive evaluation theory, competitive outcome(viz., winning vs. losing) and interpersonal context (viz., pressured vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
231
0
17

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(278 citation statements)
references
References 24 publications
17
231
0
17
Order By: Relevance
“…Deutsch (1949) defined competition in purely situational terms -as a setting in which the goal attainment of participants is negatively linked, so that the success of one participant comes at the failure of the other. Following from this definition, studies on inter-individual competition have typically examined participants in a laboratory setting, pitting them against one another or against confederates of the experimenter (e.g., Beersma, Hollenbeck, Humphrey, Moon, & Conlon, 2003;Deci, Betley, Kahle, Abrams, & Porac, 1981;Reeve and Deci, 1996;Scott & Cherrington, 1974;Stanne, Johnson, & Johnson, 1999;Tauer & Harackiewicz, 1999). For example, participants are paired with a confederate and told to try to complete more puzzles than this person (Deci et al, 1981).…”
Section: Background and Theory Development Prior Research On Competitionmentioning
confidence: 99%
“…Deutsch (1949) defined competition in purely situational terms -as a setting in which the goal attainment of participants is negatively linked, so that the success of one participant comes at the failure of the other. Following from this definition, studies on inter-individual competition have typically examined participants in a laboratory setting, pitting them against one another or against confederates of the experimenter (e.g., Beersma, Hollenbeck, Humphrey, Moon, & Conlon, 2003;Deci, Betley, Kahle, Abrams, & Porac, 1981;Reeve and Deci, 1996;Scott & Cherrington, 1974;Stanne, Johnson, & Johnson, 1999;Tauer & Harackiewicz, 1999). For example, participants are paired with a confederate and told to try to complete more puzzles than this person (Deci et al, 1981).…”
Section: Background and Theory Development Prior Research On Competitionmentioning
confidence: 99%
“…There is some evidence for the importance of the way that achievement goals are promoted. First, Reeve and Deci (1996) showed that being pressured to outperform an opponent when working on an interesting puzzle solving task led to less subsequent intrinsic motivation compared to competing against an opponent under more informational circumstances. Second, similar findings were reported in a correlational study by Ciani, Middleton, Summers, and Sheldon (2010) who found that a performance-approach classroom structure was no longer negatively related to students' personal mastery-approach…”
Section: Theoretical Considerations One Question That May Arise At Tmentioning
confidence: 99%
“…Specifically, athletes who perceived their coaches to predominantly display autocratic and controlling behaviours demonstrated less intrinsic motivation. These findings indicate that it may not be the reward per se that undermines intrinsic motivation, but the way suggests that rewards which are delivered in a controlling and pressuring interpersonal context 3 will undermine intrinsic motivation (Reeve & Deci, 1996;Vansteenkiste & Deci, 2003).…”
Section: Motivation and Autonomy-supportive And Controlling Interpersmentioning
confidence: 99%